2012
DOI: 10.1523/jneurosci.0440-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Hearing an Illusory Vowel in Noise: Suppression of Auditory Cortical Activity

Abstract: Human hearing is constructive. For example, when a voice is partially replaced by an extraneous sound (e.g., on the telephone due to a transmission problem), the auditory system may restore the missing portion so that the voice can be perceived as continuous (Miller and Licklider, 1950; for review, see Bregman, 1990; Warren, 1999). The neural mechanisms underlying this continuity illusion have been studied mostly with schematic stimuli (e.g., simple tones) and are still a matter of debate (for review, see Petk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 87 publications
5
24
0
Order By: Relevance
“…The 3-Hz phase effects could then reflect the suppression of the irrelevant phonetic cues that would not be compatible with the perceived word. This would be consistent with recent findings showing that LFO encode phonemic information (Di Liberto et al 2015) and that theta (3-5 Hz) oscillations are involved in phonemic restoration (Riecke et al 2009(Riecke et al , 2012Strauss et al 2014;Sunami et al 2013).…”
Section: Brain Oscillatory Mechanisms Of Linguistic Parsingsupporting
confidence: 93%
“…The 3-Hz phase effects could then reflect the suppression of the irrelevant phonetic cues that would not be compatible with the perceived word. This would be consistent with recent findings showing that LFO encode phonemic information (Di Liberto et al 2015) and that theta (3-5 Hz) oscillations are involved in phonemic restoration (Riecke et al 2009(Riecke et al , 2012Strauss et al 2014;Sunami et al 2013).…”
Section: Brain Oscillatory Mechanisms Of Linguistic Parsingsupporting
confidence: 93%
“…Thus, neurons with complex tuning properties or even those modulated by components of a task (Brosch et al 2005;Fritz et al 2005) may contribute to the construction of a perceptual representation; but by themselves do not offer direct evidence of a perceptual representation. There has been a recent set of literature implicating A1 in auditory perceptual decision-making (Riecke et al 2009;Kilian-Hutten et al 2011;Niwa et al 2012;Riecke et al 2012;. In one study, ferrets were asked to report changes in a sound's pitch, and it was found that both local-field potentials and spiking activity in A1 were modulated by the ferrets' pitch judgments.…”
Section: Neural Correlates Of Auditory Perception Along the Ventral Amentioning
confidence: 99%
“…Samuel's paradigm 22 ). Our method subscribes to the latter approach, also referred to as 'filling-in', which emphasizes the signal detection strategy followed in cases where a listener classification is inconsistent with the token absence in a gap 3,[23][24][25][26][27][28][29] . As has been noted 30 , from the listener's utilitarian perspective, this effect of induction in a challenging environment is not aimed at the production of decision errors (or illusions) but to assist against masking.…”
Section: Discussionmentioning
confidence: 99%
“…For human listeners, there is evidence that such compensatory principles may extend to disruptions to dynamically modulated sound, including amplitude-modulated (AM) sound, single vowels, and consonants within words 8,9,24,28,36,37 , the latter of which fall under the concept of phonemic restoration 1,3,22 . Depending on stimulus, neural correlates have been localized to different areas, including Heschl's gyrus for missing AM noise 36 , the posterior aspect of superior temporal gyrus for disrupted vowels 28 , and wider brain networks including the superior temporal lobe in the case of missed phonemes 24,37 .…”
Section: Cc-by 40 International License Peer-reviewed) Is the Authormentioning
confidence: 99%
See 1 more Smart Citation